Prophet and politician dining around the same table: God’s message in conflict? - Resane, K. Thomas (Verbum et ecclesia, 2023)
The research problem in this article is the modern prophets who rub shoulders with politicians. The focus is on the prophets found in New Prophetic Churches (NPCs). These prophets seek favours as much as politicians seek favours that are divinely sanctioned by prophets. The objectives here include ensuring that God’s message is not conflicted because of this prophet-politician symbiosis. It warns Christians not to commodify faith in order to achieve some political ambitions. The foundation is laid on biblical teachings on prophets and prophecy. There are two identified categories of the Old Testament prophets. Those who feasted with the kings at dinner tables and those who suffered under the status quo. These were banished, exiled, always on a run, and sometimes beheaded. Real-world examples of modern politicians who visit prophets on a regular basis are offered using social media and literature evaluations as resources. These politicians do so for a variety of reasons, including seeking spiritual affirmation and expressions of appreciation, praying for divine intervention during times of crisis that may affect their political careers or performances, and eventually soliciting favours. These favours are sought in some ungodly exchanges with expectations of some kickbacks. The solution to this compromise is the calling for the revisit of application of doctrinal and ethical dealings in and by the church and the government. Theology’s task is to clarify to citizens the relationship between church and government. The debate between these two powers (prophet and politician) should continue towards amicable understanding. The church must redefine its political involvement to avoid being swallowed up, and to remain the salt of the earth and a light in the world. Intradisciplinary and/or interdisciplinary implications: The article’s intradisciplinary implication is realised through the literature and social media platforms reviews to enhance social and some theological disciplines such as biblical studies, church history, ecclesiology and pneumatology. Social disciplines such as sociology, anthropology, and psychology combined with theological disciplines argue that prophets and politicians should not become bedfellows unless for enacting social justice and this to be done ethically without any compromise to morality.